Kepribadian Islami dan Kualitas Kepemimpinan - Paryontri, Ramon Ananda (Unisia, 2018)
The aim of writingthis paper is to discuss the effect of Islamic personality toward leadership quality. Individual that has Islamic personality will give effect on the leadership quality especially in the way he manages the members or the group. This paper will discuss in detail the scope of the Islamic personality, factors that affect the formation of the Islamic personality, personality aspects of islam and its effect on the quality of the leadership of the Islamic personality of a person. Good personality has been described in the Quran and exemplified by the Prophet Muhammad to form a good personality. Islamic personality is an ideal illustration for moslem individuals who can run with good religion. The Islamic personality ultimately shapes the powerful character and ultimately affects the quality of leadership of the individual him/herself. The quality of individual leadership to the organization he leads can be seen from the social maturity, emotional maturity, good interpersonal relationship, ability to solve problems, and accuracy in making decisions. Basically, the quality of leadership is strongly influenced by a good personality and Islamic personality is the key for individuals in developing the quality of life, including in terms of leadership.